2020
DOI: 10.1177/0036850420940878
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of freeway interchange merging areas based on driver workload theory

Abstract: Prior safety evaluations of interchange merging areas have mostly focused on traffic conflicts and operating speeds, without considering how these factors can influence the driver workload. Researches regarding the level of driver workload have largely concentrated on urban roads, tunnel sections, and basic freeway segments, without considering the impact of merging traffic flows on safety. Therefore, this study has investigated how merging vehicles can impact through-driver workload and safety. Three independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Our experimental results indicated that transition zone length, driving behavior, and lane closure form all have an impact on the driving workload and vehicle speed in the work zone. This experiment was conducted under free-flow conditions, and previous studies have indicated that the driving workload while merging is positively correlated with traffic volume [37], and an increase in traffic volume can lead to a decrease in vehicle speed. Part of the work zone can be borrowed from the opposite lane to form a cross-work zone, with short intervals between the transition area and median opening, which can result in a rapid rise in driving workloads within a short period of time, increasing traffic safety risks.…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental results indicated that transition zone length, driving behavior, and lane closure form all have an impact on the driving workload and vehicle speed in the work zone. This experiment was conducted under free-flow conditions, and previous studies have indicated that the driving workload while merging is positively correlated with traffic volume [37], and an increase in traffic volume can lead to a decrease in vehicle speed. Part of the work zone can be borrowed from the opposite lane to form a cross-work zone, with short intervals between the transition area and median opening, which can result in a rapid rise in driving workloads within a short period of time, increasing traffic safety risks.…”
Section: Discussionmentioning
confidence: 99%
“…Although the merging area account for a small proportion of the highway, trafc accidents occurred in this area account for a large percentage. For example, during the period from 2014 to 2016, the total length of interchanges in a province in eastern China accounted for about 9.5% of highway in this province but the number of accidents accounted for 34.5% of the total number of highway accidents, and it accounted for 24.95% of the total number of fatalities in the province [1]. In a statistical study in the United States, it also showed that accidents occurred in the highway interchanges accounted for 18% of the total number of accidents and the percentage of fatal accidents is 21.8% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Te longitudinal and lateral vehicles in the intertwined area lack coordination [1], resulting in signifcant diferences in vehicle speeds and frequent lane changes [2]. Terefore, interchanges have become bottleneck areas that restrict the operational efciency and safety of highways, representing high-risk road sections where conficts and collisions are likely to occur [3,4]. Research indicates that the occurrence of accidents is infuenced by factors such as vehicle speed, trafc fow, driver characteristics, and road geometry.…”
Section: Introductionmentioning
confidence: 99%